Предмет: Алгебра,
автор: respoison
Помогите пожалуйста!
Приложения:
Ответы
Автор ответа:
0
x/(x+2)-[(x-2)²/2]·[1/(x²-4)+1/(x²-4x+4)]=
=x/(x+2)-[(x-2)²/2]·[1/((x-2)(x+2))+1/(x-2)²]=
=x/(x+2)-[(x-2)²/2]·[(x-2)/((x-2)²(x+2))+(x+2)/((x-2)²(x+2))]=
=x/(x+2)-[(x-2)²/2]·[((x-2)+(x+2))/((x-2)²(x+2))]=
=x/(x+2)-[(x-2)²/2]·[2x/((x-2)²(x+2))]=x/(x+2)-x/(x+2)=0
т.о x/(x+2)-[(x-2)²/2]·[1/(x²-4)+1/(x²-4x+4)] не зависит от х
=x/(x+2)-[(x-2)²/2]·[1/((x-2)(x+2))+1/(x-2)²]=
=x/(x+2)-[(x-2)²/2]·[(x-2)/((x-2)²(x+2))+(x+2)/((x-2)²(x+2))]=
=x/(x+2)-[(x-2)²/2]·[((x-2)+(x+2))/((x-2)²(x+2))]=
=x/(x+2)-[(x-2)²/2]·[2x/((x-2)²(x+2))]=x/(x+2)-x/(x+2)=0
т.о x/(x+2)-[(x-2)²/2]·[1/(x²-4)+1/(x²-4x+4)] не зависит от х
Похожие вопросы
Предмет: Русский язык,
автор: bezrukovalera24
Предмет: История,
автор: alesy198018
Предмет: Химия,
автор: romasevskijvitalij25
Предмет: Математика,
автор: sofi2000q